Code-Switching Used by Cinta Laura and Yoshi Sudarso on Puella Podcast: Dulu Mau Jadi Guru, Sekarang Masuk Hollywood (A Sociolinguistic Approach) (Sastra Inggris UNPAM, 2025)
Code-switching, the alternation between languages within conversations, reflects complex linguistic and cultural phenomena. This study examines code-switching in the bilingual podcast